1996
DOI: 10.1093/geronb/51b.1.p3
|View full text |Cite
|
Sign up to set email alerts
|

Observed Affect in Nursing Home Residents with Alzheimer's Disease

Abstract: A method for assessing affect states among older people with Alzheimer's disease was developed for use in a study designed to evaluate a special care unit for such residents of a nursing home. The 6-item Philadelphia Geriatric Center Affect Rating Scale was designed for the use of research and other staff in assessing positive affect (pleasure, interest, contentment) and negative affect (sadness, worry/anxiety, and anger) by direct observation of facial expression, body movement, and other cues that do not dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
286
0
7

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 343 publications
(304 citation statements)
references
References 26 publications
11
286
0
7
Order By: Relevance
“…Three approaches to the assessment of QOL can be distinguished: self-reports by the individual with dementia (e.g., Brod et al, 1999;Logsdon et al, 2002;., ZOOO), proxy reports by a family member or caregiver (e.g., Albert et al, 2000;Rabins et al, 1999), and direct observation of behaviors assumed to be related to QOL (e.g., Fossey et al, 2002;Lawton et al, 1996;Logsdon et al, 2002). Self-ratings will be influenced by education, memory, and attention problems.…”
Section: Methodological Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Three approaches to the assessment of QOL can be distinguished: self-reports by the individual with dementia (e.g., Brod et al, 1999;Logsdon et al, 2002;., ZOOO), proxy reports by a family member or caregiver (e.g., Albert et al, 2000;Rabins et al, 1999), and direct observation of behaviors assumed to be related to QOL (e.g., Fossey et al, 2002;Lawton et al, 1996;Logsdon et al, 2002). Self-ratings will be influenced by education, memory, and attention problems.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…Direct observation of behaviors believed to be associated with QOL has the advantage that it can be based on predefined behaviors and rated consistently over time. Evaluations of observed affect (Lawton et al, 1996(Lawton et al, , 2000 and pleasant events (Logsdon & Teri, 1997) have been proposed t o measure observable attributes of QOL. Limitations of this approach include uncertainty about whether what is being observed is what an individual considers t o be important to his or her QOL.…”
Section: Observational Methodsmentioning
confidence: 99%
“…Affect was measured using the Philadelphia Geriatric Center Affect Rating Scale (ARS; Lawton, Van Haitsma, & Klapper, 1996). The observational scale has descriptive indicators for six affective states: pleasure, anger, anxiety, depression, interest, and contentment.…”
Section: Instrumentsmentioning
confidence: 99%
“…), and examples of indicators (possible bodily responses) that reflected these states (Kinney and Rentz 2005;Lawton, Van Haitsma, and Klapper 1996). Unlike many studies that use observation schedules, the design researchers in this study observed participants throughout the entire workshops (not for intermittent periods).…”
Section: Ethics Approval Was Granted Through the Human Research Ethicmentioning
confidence: 99%